Studi Kasus Pertunjukan Atraksi Tatung Pada Perayaan Festival Cap Go Meh Untuk Meningkatkan Kunjungan Wisatawan Di Kota Singkawang - Stevenson, David; S. Soeprapto , Vishnuvardhana (Jurnal Syntax Fusion, 2023)
Indonesia is a unitary state that is very rich in cultural diversity from Sabang to Merauke. Every existing culture has its own uniqueness so that it can become a tourist attraction to attract the attention of tourists, one of which is the Tatung attraction show in Singkawang City, West Kalimantan. This research was conducted with the aim of examining the Tatung culture in depth from the historical, ritual, and development aspects that have been carried out to date. This research is a type of qualitative research with a case study method. Data collection techniques were carried out through observation, interviews and documentation with four informants who had links and knowledge of Tatung culture. The results of this study found that the Tatung culture is a culture that has existed from ancient times and has been continued to the present where the peak of the celebration of the Tatung culture is the fifteenth day after the Chinese New Year which is celebrated at the Cap Go Meh Festival. Tatung culture at the Cap Go Meh Festival celebration has the potential to become a tourist attraction so development efforts are being made, such as government contributions, strategy implementation, and community support, and are carried out consistently every year.